The reciprocal interaction of sympathetic nervous system and cAMP-PKA-NF-kB pathway in immune suppression after experimental stroke. (3rd August 2016) - Zuo, Lei; Shi, Luhang; Yan, Fuling
Highlights: Activation of SNS is a significance cause of Immune suppression after acute stroke, but not able to fully elucidate the mechanism. There may be another underlying molecular pathway accounting for Immune suppression by the activation of SNS after stroke. According to SNS activation after stroke, epinephrine activated cAMP-PKA-NF-kB pathway. Abstract: Background: Sympathetic nervous system(SNS) is involved in the mechanism of immune suppression after stroke. Furthermore, as the pro-inflammatory effect of nuclear factor kappa B(NF-kB) is inhibited after stroke, which is regulated by cyclic adenosine monophosphate(cAMP) and proteinkinase A(PKA). The cAMP-PKA-NF-kB pathway might play an important role in noradrenergic-mediated immune dysfunction. Aim: The purpose of our research is to analyze how SNS interfere with the immune system after acute stroke and the underlying mechanism of cAMP-PKA-NF-kB pathway in regulating the inflammation. Methods: 32 healthy male Sprague-Dawley rats were divided into 4 groups equally and randomly (1) Sham operation group; (2) middle cerebral artery occlusion; (MCAO) control group; (3) propranolol MCAO group; (4) isopropylarterenol sham group. 72 h later after MCAO or sham operation, tumor necrosis factor-α(TNF-α)and interleukine-10(IL-10) in serum as well as cAMP, PKA and NF-kB in spleen cells were tested. Results: TNF-α decreased while IL-10 increased in serum after acute ischemia stroke (p < 0.05). Meanwhile, the levels of cAMP and PKA in spleen both increased in MCAO model while the expression of NF-kB was inhibited (p < 0.05). When propranolol was used to inhibit SNS, all of the results reversed (p < 0.05). But the reversed results were still significantly different from the sham operation group (p < 0.05). Isopropylarterenol administrated rats appeared the same trend as MCAO group when compared to the sham operation group (p < 0.05). However, the differences still existed (p < 0.05). Conclusion: On account of the SNS activation after stroke, epinephrine activates the expression of cAMP, which further increases the level of PKA. Therefore, the level of nuclear factor NF-kB is down-regulated. Since the pro-inflammatory effect of NF-kB slacked, the immune system may be inhibited after stroke.